Addressing how spatial resolution affects image velocimetry outputs: implications for measurements from space - Harley Dixey; Edward Rollason; Stuart Dunning; Matthew Thomas Perks (Hydrological Sciences Journal, 2026)

GLOF hazard, exposure, vulnerability, and risk assessment of potentially dangerous glacial lakes in the Bhutan Himalaya - Sonam Rinzin; Guoqing Zhang; Ashim Sattar; Sonam Wangchuk; Simon K. Allen; Stuart Dunning; Menger Peng (Journal of Hydrology, 2023)

Revising supraglacial rock avalanche magnitudes and frequencies in Glacier Bay National Park, Alaska - William D. Smith; Stuart A. Dunning; Neil Ross; Jon Telling; Erin K. Jensen; Dan H. Shugar; Jeffrey A. Coe; Marten Geertsema (Geomorphology, 2023)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Geophysical surveys of the sediments of Loch Ness, Scotland: implications for the deglaciation of the Moray Firth Ice Stream, British–Irish Ice Sheet - Andrew J. Turner; John Woodward; Stuart A. Dunning; Adrian J. Shine; Chris R. Stokes; Colm Ó Cofaigh (Journal of Quaternary Science, 2012)
We present results from three geophysical campaigns using high‐resolution sub‐bottom profiling to image sediments deposited in Loch Ness, Scotland. Sonar profiles show distinct packages of sediment, providing insight into the loch's deglacial history. A recessional moraine complex in the north of the loch indicates initial punctuated retreat. Subsequent retreat was rapid before stabilisation at Foyers Rise formed a large stillstand moraine. Here, the calving margin produced significant volumes of laminated sediments in a proglacial fjord‐like environment. Subsequent to this, ice retreated rapidly to the southern end of the loch, where it again deposited a sequence of proglacial laminated sediments. Sediment sequences were then disturbed by the deposition of a thick gravel layer and a large turbidite deposit as a result of a jökulhlaup from the Spean/Roy ice‐dammed lake. These sediments are overlain by a Holocene sheet drape. Data indicate: (i) a former tributary of the Moray Firth Ice Stream migrated back into Loch Ness as a major outlet glacier with a calving margin in a fjord‐like setting; (ii) there was significant sediment supply to the terminus of this outlet glacier in Loch Ness; and (iii) that jökulhlaups are important for sediment supply into proglacial fjord/lake environments and may compose >20% of proglacial sedimentary sequences. Copyright © 2011 John Wiley & Sons, Ltd.

Trends in landslide occurrence in Nepal - David N. Petley; Gareth J. Hearn; Andrew Hart; Nicholas J. Rosser; Stuart A. Dunning; Katie Oven; Wishart A. Mitchell (Natural Hazards, 2007)